PENGARUH PENERAPAN MEDIA HAND PUPPET TERHADAP PEMAHAMAN KONSEP ATURAN DI RUMAH DAN DI SEKOLAH PADA SISWA KELAS II SDN 21 PEKANBARU - Hamidah; Elpri Darta Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The results of the preliminary interviews showed that some students still experienced difficulties in understanding and applying the concept of rules in their daily lives. This condition was related to the limited use of instructional media, which resulted in students having insufficient concrete and engaging learning experiences to support their understanding of the material. One alternative that can be used to address this condition is the implementation of hand puppet media. Therefore, this study aimed to examine and determine whether the implementation of hand puppet media affected students’ understanding of the concept of rules at home and at school among second-grade students at SDN 21 Pekanbaru. This study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The population consisted of 95 second-grade students at SDN 21 Pekanbaru in the 2025–2026 academic year. A sample of 55 students was selected using purposive sampling, consisting of 30 students in the experimental group from class II A and 25 students in the control group from class II C. The results showed that the implementation of hand puppet media had a significant effect on students’ understanding of the concept of rules at home and at school. This finding was supported by the hypothesis test using an Independent Samples t-test, which yielded a Sig. (2-tailed) value of 0.018. Since the value was lower than the 0.05 significance level (0.018 < 0.05), there was a significant difference in students’ conceptual understanding between the experimental and control groups.